Analysis of Climatic Model Using Fractional Optimal Control - Muhammad Nadeem; Mustafa Habib; Muntaha Safdar; Patrick Kandege Mwanakatwe (Journal of Mathematics)
CO2 emissions are one of the most critical and challenging problems impacting the atmosphere. In order to reduce CO2 emissions, significant efforts must be put forward in advanced research. In this research, we propose a fractional optimal control approach to effectively deal with the accessible resources and minimize the restriction of variables. The mathematical model is formulated in terms of the Caputo fractional derivative. The formulated problem is numerically solved using a forward-backward sweep approach with the generalized Euler method. We present a numerical problem to obtain the optimal solution and show that the suggested process is very efficient in science and engineering problems.